Sosialisasi Pentingnya ASI Ekslusif untuk Mencegah Kejadian Wasting pada Balita - Umar, Mareza Yolanda; Wardani, Psiari Kusuma; Ayu, Juwita Desri; Putri, Nopi Anggista; Primadevi, Inggit (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Malnutrition, especially wasting, in children is a major public health problem and one of the most common causes of morbidity and death in the world. About 800,000 children under the age of 5 are estimated to die because of wasting, and about 60% is caused by severe wasting Wasting can be prevented by exclusively breastfeeding. The purpose of this community service is to provide counseling about the importance of exclusive breastfeeding to prevent wasting events in toddlers. Methodology: This community service will be held in Pekon Sidokaton, with a total of participants is 35. Carried out by providing outreach using the lecture method assisted by Leaflets and PPT as well as questions and answers about the importance of exclusive breastfeeding given to postpartum mothers and posyandu cadres. Results: All participants expressed enthusiasm and responded to the counseling activity. After being explained, participants became more aware of the importance of exclusive breastfeeding in preventing wasting in toddler. Conclusions: Exclusive breastfeeding can prevent wasting in infants, leading to improved child well-being in the present and contributing to long-term human capacity development. Increasing efforts to promote exclusive breastfeeding during the first six months of life is essential to ensure proper nutritional intake, healthy infant growth, and support nutrition-related and culturally appropriate interventions.. Limitations: This community service is only carried out in one pekon, namely the Pekon Sidokaton where the Gisting sub-district has 9 pekons, of course it is still very insufficient to reduce the number of wasting incidents. Contribution: The results of this community service is hoped that will be increase the focus on promoting exclusive breastfeeding during the first 6 months of life, which is necessary to ensure proper nutritional intake and healthy growth of babies and promote interventions that are related to nutrition and cultural.